Condensed Matter Nuclear Science 2005
DOI: 10.1142/9789812701510_0044
|View full text |Cite
|
Sign up to set email alerts
|

Charged-Particle Emissions From Deuterided Metals

Abstract: We present evidence for energetic charged particles emanating from partiallydeuterided titanium foils (TiDx) subjected to non-equilibrium conditions. To scrutinize emerging evidence for low-temperature nuclear reactions, we investigated particle yields employing three independent types of highly-sensitive, segmented particle detectors over a six-year period. One experiment measuring neutron emission from TiDx foils showed a background-subtracted yield of 57 ± 13 counts per hour. (The neutron experiments are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The ratio of 3 He/ 4 He in a dissolved gas sample extracted from well water in June 2000 and corrected for air contamination is 12.0 R A . The helium-enriched component and high 3 He/ 4 He ratio in the NSF well clearly indicate a mantle plume-magmatic source for the helium [27] . In contrast, the tritium concentrations in the samples collected after water dilution events are similar to those of the precipitation, and to water in the cistern at the wellhead [27] (Fig.…”
Section: Anomalous Tritium At Kilauea Volcano and Other Volcanoesmentioning
confidence: 82%
See 1 more Smart Citation
“…The ratio of 3 He/ 4 He in a dissolved gas sample extracted from well water in June 2000 and corrected for air contamination is 12.0 R A . The helium-enriched component and high 3 He/ 4 He ratio in the NSF well clearly indicate a mantle plume-magmatic source for the helium [27] . In contrast, the tritium concentrations in the samples collected after water dilution events are similar to those of the precipitation, and to water in the cistern at the wellhead [27] (Fig.…”
Section: Anomalous Tritium At Kilauea Volcano and Other Volcanoesmentioning
confidence: 82%
“…The other volcanoes were not hot-spot volcanoes, i.e. the most component in the magmatic fluids may not tap from deep mantle, tapping instead from much shallower magmas [27] . Therefore, 3 He/ 4 He ratios, probably including 3 H, in these magmatic fluids should be much less than those at Kilauea Volcano.…”
Section: Anomalous Tritium At Kilauea Volcano and Other Volcanoesmentioning
confidence: 99%
“…Based on known solid state and nuclear physics, d-d fusion is not expected in TiD x . Hence, we consider these experimental results to represent a new and unique physical process noted in Equation 1. We have shown that special treatments are important to produce the recorded effects; such as metal processing, grooving foil samples, gas and acid loading, and applying strong dc currents to enhance non-equilibrium conditions within foils.…”
Section: Resultsmentioning
confidence: 99%